RAP30/74: a general initiation factor that binds to RNA polymerase II. - Burton, Z F (1988)
We have previously shown by affinity chromatography that RAP30 and RAP74 are the mammalian proteins that have the highest affinity for RNA polymerase II. Here we show that RAP30 binds to RAP74 and that the RAP30-RAP74 complex (RAP30/74) is required for accurate initiation by RNA polymerase II. RAP30/74 is required for accurate transcription from the following promoters: the adenovirus major late promoter, the long terminal repeat of human immunodeficiency virus, P2 of the human c-myc gene, the mouse beta maj-globin promoter (all of which have TATA boxes), and the mouse dihydrofolate reductase promoter (which lacks a TATA box). RAP30/74 is not required for initiation by RNA polymerase III at the adenovirus virus-associated RNA promoters. Therefore, RAP30/74 is a general initiation factor that binds to RNA polymerase II.